Sulfide solid electrolyte and preparation method and application thereof

By preparing the sulfide solid electrolyte composed of Li7Si2S7X, the problems of low ionic conductivity and poor stability to lithium metal in the existing sulfide solid electrolyte are solved, and the electrochemical performance of high-energy density batteries is improved.

CN119695256AActive Publication Date: 2025-03-25HUAZHONG UNIV OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411716612.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-25
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

The low ionic conductivity of existing sulfide solid electrolytes and low stability to lithium metal limit their application in high energy density batteries.

Method used

A sulfide solid electrolyte is provided, which consists of Li7Si2S7X, wherein X is one or more of Cl, Br, I, and is prepared by mixing, ball milling and calcining in an inert gas atmosphere.

Benefits of technology

It improves the ionic conductivity of sulfide solid electrolytes, and significantly improves the stability to lithium metal in all-solid lithium batteries, supporting high-energy density lithium battery applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695256A_ABST
    Figure CN119695256A_ABST
Patent Text Reader

Abstract

The invention discloses a sulfide solid electrolyte as well as a preparation method and application thereof, the composition of the sulfide solid electrolyte is Li7Si2S7X, and X is one or more of Cl, Br and I. The sulfide solid electrolyte provided by the invention has relatively high ionic conductivity, and has high stability to lithium metal in an all-solid-state lithium battery, so that the lithium metal with high energy density can be used as a negative electrode material, and the electrochemical performance of the solid-state battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid-state batteries, and in particular relates to a sulfide solid electrolyte and a preparation method and application thereof. Background Art

[0002] All-solid-state batteries refer to batteries with a solid electrolyte layer between the positive electrode layer and the negative electrode layer. All-solid-state batteries use solid electrolytes instead of liquid electrolytes in traditional lithium-ion batteries to reduce flammability, increase the cycle life of the battery, and make alkali metal negative electrodes available, thereby further improving the energy density and safety of lithium-ion batteries, making them the most promising next-generation lithium-ion batteries.

[0003] At present, solid electrolytes can be divided into three categories: inorganic solid electrolytes, polymer solid electrolytes, and composite solid electrolytes. Inorganic solid electrolytes include oxide inorganic solid electrolytes, sulfide inorganic solid electrolytes, etc. Among them, sulfur has a large atomic radius and polarizability, which causes lattice distortion to form larger ion channels. In addition, the binding force between sulfur and lithium ions is weak, and the number of mobile carriers in the system is large. Therefore, sulfide solid electrolytes exhibit good ionic conductivity and have become the main research object at present.

[0004] However, current sulfide solid electrolytes suffer from low ionic conductivity and low stability toward lithium metal, which limits their application in high energy density batteries. Summary of the invention

[0005] In view of the deficiencies of the prior art, the object of the present invention is to provide a sulfide solid electrolyte and a preparation method and application thereof, so as to solve the problems of low ionic conductivity and low stability to lithium metal of the existing sulfide solid electrolyte.

[0006] To achieve the above object, the present invention is implemented through the following technical solutions: On the one hand, the present invention provides a sulfide solid electrolyte, the composition of which is Li7Si2S7X, wherein X is one or more of Cl, Br, and I.

[0007] Preferably, the composition of the sulfide solid electrolyte is Li7Si2S7I a X (1-a) , wherein X is one or more of Cl and Br, and 0<a≤1. More preferably, 0.4≤a≤0.6, for example, a can be 0.4, 0.5, 0.6, etc.

[0008] Preferably, the sulfide solid electrolyte has an argyrodite-type crystal phase structure.

[0009] On the other hand, the present invention also provides a method for preparing the sulfide solid electrolyte according to the first aspect, comprising the following steps: (1) According to the stoichiometric ratio of elements in Li7Si2S7X, a lithium source, a silicon source, a sulfur source and an X source are mixed in an inert gas atmosphere to obtain a mixture; (2) ball milling the mixture in an inert gas atmosphere to obtain a precursor powder; (3) The precursor powder is calcined in an inert gas atmosphere to obtain a sulfide solid electrolyte.

[0010] Preferably, in step (1), the lithium source is one or more of Li2S, LiI, LiCl, and LiBr; the silicon source is SiS2; and the sulfur source is one or more of Li2S, SiS2, and Li2S2.

[0011] Preferably, in step (1), the X source is one or more of LiI, LiCl, and LiBr.

[0012] Preferably, the ball milling speed in step (2) is 300-700 rpm, and the ball milling time is 5-20 h.

[0013] Preferably, the calcination temperature in step (3) is 350-700° C., and the calcination time is 1-5 h.

[0014] In a third aspect, the present invention provides an all-solid-state battery, comprising a positive electrode layer, a negative electrode layer and a solid electrolyte layer, wherein the solid electrolyte layer is the sulfide solid electrolyte described in the first aspect.

[0015] Preferably, the positive electrode of the all-solid-state battery comprises LiNi 0.7 Mn 0.1 Co 0.2 O2 and the sulfide solid electrolyte described in the first aspect, the negative electrode is a lithium metal sheet.

[0016] The beneficial effects of the present invention are: The sulfide electrolyte provided by the present invention has high ionic conductivity and high stability to lithium metal in an all-solid-state lithium battery, so that lithium metal with high energy density can be used as a negative electrode material to improve the electrochemical performance of the solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 is the XRD pattern of the sulfide solid electrolyte prepared in Examples 1 to 3; Figure 2 is a conductivity diagram of the sulfide solid electrolyte prepared in Examples 1 to 3; Figure 3It is a cycle performance diagram of the all-solid-state battery prepared by the sulfide solid electrolyte prepared in Examples 1 to 3. DETAILED DESCRIPTION

[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] The embodiment of the present invention provides a sulfide solid electrolyte, wherein the composition of the sulfide solid electrolyte is Li7Si2S7X, wherein X is one or more of Cl, Br, and I. Preferably, the composition of the sulfide solid electrolyte is Li7Si2S7I a X (1-a) , wherein X is one or more of Cl, Br, and 0<a≤1.

[0020] In some embodiments, the sulfide solid electrolyte has an argyrodite-type crystal phase structure.

[0021] The present invention also provides a method for preparing a sulfide solid electrolyte, comprising the following steps: (1) According to the stoichiometric ratio of elements in Li7Si2S7X, a lithium source, a silicon source, a sulfur source and an X source are mixed in an inert gas atmosphere to obtain a mixture; (2) In an inert gas atmosphere, the mixture is ball-milled at a speed of 300-700 rpm for 5-20 h to obtain a precursor powder; (3) In an inert gas atmosphere, calcining the precursor powder at 350-700°C for 1-5h to obtain a sulfide solid electrolyte.

[0022] Wherein, in step (1), the lithium source is one or more of Li2S, LiI, LiCl, and LiBr; the silicon source is SiS2; the sulfur source is one or more of Li2S, SiS2, and Li2S2; and the X source is one or more of LiI, LiCl, and LiBr.

[0023] In order to further illustrate the present invention, a sulfide solid electrolyte provided by the present invention and its preparation method and application are described in detail below in combination with embodiments, but it should not be understood as limiting the protection scope of the present invention.

[0024] Example 1 Li2S, SiS2, and LiI were mixed in a glove box at a molar ratio of 3:2:1 to obtain a mixture. The mixture was placed in a 50 mL zirconium dioxide ball milling jar, and zirconium oxide balls were added, sealed, and transferred to a ball mill. Ball milling was performed at 500 rpm for 15 hours, and the ball-milled samples were collected and sealed in a vacuum quartz tube for calcination. The calcination temperature was 700 ° C, and the calcination time was 5 hours to obtain Li7Si2S7I solid electrolyte material.

[0025] Example 2 Li2S, SiS2, LiI, and LiCl were mixed in a glove box at a molar ratio of 3:2:0.5:0.5 to obtain a mixture. The mixture was placed in a 50 mL zirconium dioxide ball milling jar, and zirconium oxide balls were added, sealed, and transferred to a ball mill. Ball milling was performed at 500 rpm for 15 hours, and the ball-milled samples were collected and sealed in a vacuum quartz tube for calcination. The calcination temperature was 700 ° C and the calcination time was 5 hours to obtain Li7Si2S7I 0.5 Cl 0.5 Solid electrolyte materials.

[0026] Example 3 Li2S, SiS2, LiI, and LiBr were mixed in a glove box at a molar ratio of 3:2:0.5:0.5 to obtain a mixture. The mixture was placed in a 50 mL zirconium dioxide ball milling jar, and zirconium oxide balls were added, sealed, and transferred to a ball mill. Ball milling was performed at 500 rpm for 15 hours, and the ball-milled samples were collected and sealed in a vacuum quartz tube for calcination. The calcination temperature was 700 ° C and the calcination time was 5 hours to obtain Li7Si2S7I 0.5 Br 0.5 Solid electrolyte materials.

[0027] Example 4 Li2S, SiS2, and LiCl were mixed in a glove box at a molar ratio of 3:2:1 to obtain a mixture. The mixture was placed in a 50mL zirconium dioxide ball milling jar, and zirconium oxide balls were added, sealed, and transferred to a ball mill. Ball milling was performed at 500rpm for 15h, and the ball-milled samples were collected and sealed in a vacuum quartz tube for calcination. The calcination temperature was 700℃ and the calcination time was 5h to obtain Li7Si2S7Cl solid electrolyte material.

[0028] Example 5 Li2S, SiS2, and LiBr were mixed evenly in a glove box at a molar ratio of 3:2:1 to obtain a mixture. The mixture was placed in a 50mL zirconium dioxide ball milling jar, and zirconium oxide balls were added, sealed, and transferred to a ball mill. Ball milling was performed at 500rpm for 15h, and the ball-milled samples were collected and sealed in a vacuum quartz tube for calcination. The calcination temperature was 700℃ and the calcination time was 5h to obtain Li7Si2S7Br solid electrolyte material.

[0029] Example 6 Li2S, SiS2, LiI, and LiCl were mixed in a glove box at a molar ratio of 3:2:0.4:0.6 to obtain a mixture. The mixture was placed in a 50 mL zirconium dioxide ball milling jar, and zirconium oxide balls were added, sealed, and transferred to a ball mill. Ball milling was performed at 500 rpm for 15 hours, and the ball-milled samples were collected and sealed in a vacuum quartz tube for calcination. The calcination temperature was 700 ° C and the calcination time was 5 hours to obtain Li7Si2S7I 0.4 Cl 0.6 Solid electrolyte materials.

[0030] Example 7 Li2S, SiS2, LiI, and LiCl were mixed in a glove box at a molar ratio of 3:2:0.2:0.8 to obtain a mixture. The mixture was placed in a 50 mL zirconium dioxide ball milling jar, and zirconium oxide balls were added, sealed, and transferred to a ball mill. Ball milling was performed at 500 rpm for 15 hours, and the ball-milled samples were collected and sealed in a vacuum quartz tube for calcination. The calcination temperature was 700 ° C and the calcination time was 5 hours to obtain Li7Si2S7I 0.2 Cl 0.8 Solid electrolyte materials.

[0031] Example 8 Li2S, SiS2, LiI, and LiBr were mixed in a glove box at a molar ratio of 3:2:0.4:0.6 to obtain a mixture. The mixture was placed in a 50 mL zirconium dioxide ball milling jar, and zirconium oxide balls were added, sealed, and transferred to a ball mill. Ball milling was performed at 500 rpm for 15 hours, and the ball-milled samples were collected and sealed in a vacuum quartz tube for calcination. The calcination temperature was 700 ° C and the calcination time was 5 hours to obtain Li7Si2S7I 0.4 Br 0.6 Solid electrolyte materials.

[0032] Example 9 Li2S, SiS2, LiI, and LiBr were mixed in a glove box at a molar ratio of 3:2:0.6:0.4 to obtain a mixture. The mixture was placed in a 50 mL zirconium dioxide ball milling jar, and zirconium oxide balls were added, sealed, and transferred to a ball mill. Ball milling was performed at 500 rpm for 15 hours, and the ball-milled samples were collected and sealed in a vacuum quartz tube for calcination. The calcination temperature was 700 ° C and the calcination time was 5 hours to obtain Li7Si2S7I 0.6 Br 0.4 Solid electrolyte materials.

[0033] Example 10 Li2S, SiS2, LiI, and LiBr were mixed in a glove box at a molar ratio of 3:2:0.2:0.8 to obtain a mixture. The mixture was placed in a 50 mL zirconium dioxide ball milling jar, and zirconium oxide balls were added. The mixture was sealed and transferred to a ball mill. The ball milling was performed at 500 rpm for 15 hours, and the ball milled samples were collected and sealed in a vacuum quartz tube for calcination. The calcination temperature was 700 ° C and the calcination time was 5 hours to obtain Li7Si2S7I 0.2 Br 0.8 Solid electrolyte materials.

[0034] Performance Testing (1) XRD test Figure 1 3 is the XRD diagram of the sulfide solid electrolyte obtained in Examples 1 to 3. It can be seen from the figure that the main diffraction peaks of the obtained solid electrolyte are sharp, which proves that the solid electrolyte has good crystallinity. At the same time, the synthesized sample has a argyrodite-type crystal phase structure.

[0035] (2) Ionic conductivity test The stainless steel / electrolyte / stainless steel cell was assembled and the cell was tested using an ADMO electrochemical workstation. -1 ~10 6 The AC impedance spectrum (EIS) in the Hz frequency range was then fitted to obtain the impedance values ​​corresponding to each embodiment. Finally, the ionic conductivity was calculated according to the formula: σ = L / (R×S), where: L is the thickness of the electrolyte sheet, R is the bulk impedance of the electrolyte, and S is the surface area of ​​the electrolyte. The test results are shown in Figure 2 And as shown in Table 1.

[0036] Table 1 Ionic conductivity of sulfide electrolytes prepared in Examples 1 to 3

[0037] (3) Lithium metal stability test Preparation of all-solid-state lithium-ion battery: First, 120 mg of sulfide solid electrolyte material was pressed into a sheet with a thickness of about 0.70 mm at a pressure of 360 MPa, and pressure was applied to the groove of the battery mold for 1 minute to obtain an electrolyte sheet. 0.7 Mn 0.1 Co 0.2 O2, sulfide solid electrolyte material and VGCF were mixed evenly in a mass ratio of 7:2.8:0.2 to obtain a positive electrode composite material. Subsequently, 2 mg of the above positive electrode composite material was evenly distributed on one side of the electrolyte sheet and maintained at a pressure of 300 MPa for 30 s. Finally, a lithium metal negative electrode was placed on the other side of the electrolyte sheet and a pressure of 60 MPa was applied to obtain an all-solid-state lithium battery.

[0038] The cycle performance of solid-state lithium batteries was tested at 0.5C and room temperature. Figure 3 As shown. Figure 3 It can be seen that the all-solid-state batteries assembled using the solid electrolytes of Examples 1 to 3 have better discharge capacity and cycle stability, indicating that the sulfide solid electrolyte provided by the present invention has good lithium metal stability and can be used to prepare high energy density lithium batteries.

[0039] It should be noted that the above embodiments all belong to the same inventive concept, and the description of each embodiment has its own focus. For matters that are not described in detail in some embodiments, reference may be made to the description in other embodiments.

[0040] The above-mentioned embodiments only express the implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.

Claims

1. A sulfide solid electrolyte, characterized in that: The composition of the sulfide solid electrolyte is Li7Si2S7X, wherein X is one or more of Cl, Br, and I.

2. The sulfide solid electrolyte according to claim 1, characterized in that The composition of the sulfide solid electrolyte is Li7Si2S7I a X (1-a) , wherein X is one or more of Cl, Br, and 0<a≤1.

3. The sulfide solid electrolyte according to claim 1, characterized in that The sulfide solid electrolyte has an argyrodite-type crystal phase structure.

4. The method for preparing a sulfide solid electrolyte according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) According to the stoichiometric ratio of elements in Li7Si2S7X, a lithium source, a silicon source, a sulfur source and an X source are mixed in an inert gas atmosphere to obtain a mixture; (2) ball milling the mixture in an inert gas atmosphere to obtain a precursor powder; (3) calcining the precursor powder in an inert gas atmosphere to obtain the sulfide solid electrolyte.

5. The method for preparing a sulfide solid electrolyte according to claim 4, characterized in that: In step (1), the lithium source is one or more of Li2S, LiI, LiCl, and LiBr; the silicon source is SiS2; and the sulfur source is one or more of Li2S, SiS2, and Li2S2.

6. The method for preparing a sulfide solid electrolyte according to claim 4, characterized in that: In step (1), the X source is one or more of LiI, LiCl, and LiBr.

7. The method for preparing a sulfide solid electrolyte according to claim 4, characterized in that: The ball milling speed in step (2) is 300-700 rpm, and the ball milling time is 5-20 h.

8. The method for preparing a sulfide solid electrolyte according to claim 4, characterized in that: The calcination temperature in step (3) is 350-700°C, and the calcination time is 1-5h.

9. An all-solid-state battery, comprising a positive electrode layer, a negative electrode layer and a solid electrolyte layer, characterized in that: The solid electrolyte layer comprises the sulfide solid electrolyte according to any one of claims 1 to 3.

10. The all-solid-state battery according to claim 9, characterized in that: The positive electrode includes LiNi 0.7 Mn 0.1 Co 0.2 O2 and the sulfide solid electrolyte, and the negative electrode is a lithium metal sheet.

Citation Information

Patent Citations

  • Sulfide solid electrolyte, preparation method thereof and lithium ion battery

    CN113659199A

  • Argyrodite type sulfide solid electrolyte containing lithium halide coating layer and preparation of argyrodite type sulfide solid electrolyte

    CN114267874A

  • Sulfide solid electrolyte and preparation and application thereof

    CN114361580A

  • Sulfide solid electrolyte, preparation method thereof and all-solid-state lithium ion battery

    CN115579511A

  • SOLID SULFID ELECTROLYTE MATERIAL, BATTERY AND METHOD FOR PRODUCING THE SOLID SULFID ELECTROLYTE MATERIAL

    DE102015107399A1